Optimization of Dynamic Vibration Absorber on Ambulance Stretchers Using the Genetic Algorithm Method Based on ISO 2631 Standards - Anandika Parwata; Wiwiek Hendrowati (Engineering Proceedings, 2025)
Ambulances play a crucial role in patient transportation and are often subjected to rapid accelerations, decelerations, and maneuvering. These dynamics can cause vibrations and instability, significantly impacting patient comfort and safety. This research aims to enhance patient comfort by implementing a dynamic vibration absorber (DVA) system on the stretcher of an ambulance. The DVA incorporates additional mass connected through a damping system to reduce pitching and bouncing effects, improving comfort levels according to ISO 2631 standards. The optimization of parameters such as the distance between the stretcher’s center of gravity and the DVA, spring constants, damping coefficients, and mass is carried out using a genetic algorithm (GA). By using a half-car model and sinusoidal road profiles, this study simulates and analyzes the impact of DVA on reducing vibrations. The results demonstrate a significant improvement in patient comfort and safety during ambulance transport.